Knowledge, attitude, and practice toward family-based treatment among parents of children with leukemia - Xue Yang; Xue Yang; Shihua Long; Shihua Long; Feng Lu; Feng Lu; Zhigui Ma; Zhigui Ma (Frontiers Media S.A., 2024)
BackgroundTo investigate the KAP toward family-based treatment among parents of children with leukemia.MethodsThis cross-sectional study was conducted between December, 2022 and July, 2023 in the Pediatric hematologic oncology department of West China Second University Hospital, Sichuan University. The study population consisted of parents of children diagnosed with leukemia. Their demographic characteristics and KAP toward family-based treatment for leukemia were collected by self-administered questionnaires.ResultsA total of 482 parents participated, including 379 (78.63%) females, with an average age of 35.83 ± 6.40 years. The mean scores for KAP were 7.28 ± 1.13 (possible range: 0-10), 37.82 ± 4.38 (possible range: 9-45), and 40.09 ± 4.17 (possible range: 9-45), respectively. Multivariate logistic regression analysis indicated that the knowledge score (OR = 1.48, 95% CI: [1.08-2.05], P = 0.016), attitude score (OR = 1.31, 95% CI: [1.18-1.46], P < 0.001), education of junior college and above (OR = 11.28, 95% CI: [1.94-65.65], P = 0.007), and monthly income of 5,000-10,000 Yuan (OR = 10.88, 95% CI: [1.15-102.98], P = 0.037) were independently associated with a proactive practice. Structural equation modeling (SEM) results highlighted the significant direct impact of knowledge on attitude (β = 0.72, P = 0.002), attitude on practice (β = 0.57, P < 0.001), and knowledge on practice (β = 0.81, P < 0.001).ConclusionParents of children with leukemia demonstrated inadequate knowledge, but positive attitudes and proactive practices toward family-based treatment for leukemia. Future interventions should not only prioritize augmenting parental knowledge through educational initiatives but also focus on fostering positive attitudes and providing support for both knowledge and practical parenting skills to facilitate proactive involvement.